2010
DOI: 10.5511/plantbiotechnology.27.311
|View full text |Cite
|
Sign up to set email alerts
|

NAD+-malic enzyme affects nitrogenase activity of Mesorhizobium loti bacteroids in Lotus japonicus nodules

Abstract: A gram-negative bacterium, Mesorhizobium loti, contains a NADP ϩ -malic enzyme (mlr5329) and a malate oxidoreductase (mlr0809) in the genome. We have screened transposon-induced mutants from the signature-tagged mutant library to survey their roles in nodule nitrogenase activity. The nodules induced by malate oxidoreductase mutants failed to fix N 2 , although NADP ϩ -malic enzyme (NADP ϩ -ME) mutants induced nodules exhibiting no change in nodule nitrogenase activity. When malate-degrading enzyme activities w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…1–3; Appendix S1), and (3) maintained intact symbiosomes with relatively stable bacteroid populations (Table 3). These latter features are typical of effective nodules in legumes with determinate nodule development (Chua et al, 1985; Banba et al, 2001; Schumpp and Deakin, 2010; Thapanapongworakul et al, 2010; Chungopast et al, 2014). The features associated with the hypothesized induced cellular senescence appeared to initiate slightly earlier in L. japonicus hosts (∼5 wpi) compared to A. strigosus (∼6 wpi) consistent with the early‐flowering phenotype and faster development of the L. japonicus MG‐20 accession (Kawaguchi, 2000).…”
Section: Discussionmentioning
confidence: 88%
“…1–3; Appendix S1), and (3) maintained intact symbiosomes with relatively stable bacteroid populations (Table 3). These latter features are typical of effective nodules in legumes with determinate nodule development (Chua et al, 1985; Banba et al, 2001; Schumpp and Deakin, 2010; Thapanapongworakul et al, 2010; Chungopast et al, 2014). The features associated with the hypothesized induced cellular senescence appeared to initiate slightly earlier in L. japonicus hosts (∼5 wpi) compared to A. strigosus (∼6 wpi) consistent with the early‐flowering phenotype and faster development of the L. japonicus MG‐20 accession (Kawaguchi, 2000).…”
Section: Discussionmentioning
confidence: 88%
“…Sinorhizobium sp. NGR234 also uses both of these pathways on a variety of hosts, and M. loti and B. japonicum USDA110 may also use both pathways, on the basis that dme mutants retain some nitrogen fixation (26,142). Dme is a complex protein with N-terminal, malic enzyme, and C-terminal phosphotransacetylase (Pta) domains.…”
Section: Bacterial Carbon Metabolismmentioning
confidence: 99%
“…The NGR234 dme mutants were found to form Fix ϩ nodules with various N 2 fixation efficiencies on various host plants (see below). Moreover, while this work was under way, dme mutants of B. japonicum, R. leguminosarum, and Mesorhizobium loti were shown to form Fix ϩ nodules on soybean, pea, and Lotus, respectively (8,36,48). Together, these findings demonstrate that the N 2 fixation phenotype of dme mutants is host plant dependent and also suggest that the completely Fix Ϫ phenotype of S. meliloti dme mutants is unusual and perhaps unique to the S. meliloti-alfalfa symbiosis.…”
mentioning
confidence: 66%
“…In a symbiotic mutant screen of A. caulinodans ORS571, two insertion mutants with mutations in a malic enzyme-like gene (azc3656) were found to form Fix Ϫ nodules (47). In a subsequent study, transcription of a second malic enzyme-like gene (azc0119) was found to be much higher in A. caulinodans bacteroids than in free-living cells (48). The interpre- tation of these results was hindered by an absence of functional data on either the azc3656 or azc0119 gene product.…”
Section: Resultsmentioning
confidence: 98%